Recognition of factors affecting the use of volunteer clinical forces in hospitals in Tehran: A qualitative study - Mahdi Hasani; Hassan Abolghasem Gorji; Sirous Panahi (Wolters Kluwer Medknow Publications, 2021)
INTRODUCTION: Volunteers are valuable human resources for service-providing organizations. Health system requires their participation and cooperation in all sectors to achieve more success. The present study was conducted to recognize factors influencing the use of volunteer clinical forces (VCFs) in Tehran hospitals from 2018 to 2020. METHODS: This is a qualitative study, based on grounded theory approach, and was done through semi-structured interviews. The studied population included the experts, managers of hospitals, and high-ranking managers in the Ministry of Health, Iranian Red Crescent Organization, and health nongovernmental organizations (NGOs). Nineteen persons were selected by purposeful sampling method and interviewed. The achieved data were analyzed by content analysis method. RESULTS: The results showed that using VCFs in Tehran's hospitals was affected by eight following factors: organizational, legal, policy-making, economic, social, security, personal, and cultural dimensions. These findings illustrated the necessity of making changes in the structures, the rules, and the culture of health system to fit the bases with new approaches. CONCLUSION: VCFs amplify the quality and structure of service providing for patients in hospitals. The focus of policymakers and high-ranking managers in health system is on accelerating their use permanently and legally. Developing health-centered NGOs facilitates the access to VCF, lessens nonclinical loads of hospitals, and improves the organization of human forces. The experiences and knowledge of VCFs cause to develop hospitals' resilience, develop social participation, and improve social capitals in medical field.